Gender differences in labor allocation in West Africa : A case study of the savannas of Northern Nigeria - Chianu, Jonas N.; Tsujii, H. (2007)
Boserup’s in?uential book ‘Women’s Role in Economic Development’ generated debate on gender and development in Africa. Based on a survey of 322 households in northern Nigeria, this paper evaluates gender differences in labor allocation to eight enterprises (crop production, livestock production, processing, fuelwood activities, food gathering, trading, non-farm activities and salaried job) using weighted arithmetic mean. Results indicate that labor allocation to crop production and processing followed sex lines: men allocated most of their labor to crop production (71% by male children, 81% adult males). Women allocated most of their labor to processing (36% female children, 57% adult females). The high concentration of men’s labor on crop production is strong evidence that men, not women alone (as earlier suggested) play important role in agricultural production. The study concluded With research and policy implications ofthe observed labor allocation patterns.